Properties of T-Student Significance Test in Asymmetric GARCH Time Series Modeling - Krzysztof SZYMONIAK-KSIĄŻEK (Communications of International Proceedings, 2021)
In this paper the properties of t-Student significance test in time series modeling are discussed. In particular GARCH models are considered. Their special property is the volatility clustering effect. Apart from the classic GARCH process, tests were also carried out in the case of processes characterized by asymmetry. The paper contains t-test  simulation result for the following processes: EGARCH, TGARCH, GJR-GARCH and APARCH. The motivation for using asymmetric models is the universality of the leverage effect, i.e. a situation in which volatility tends to increase dramatically following bad news, and to increase moderately (or even to diminish) following good news.
Keywords: Asymmetry; Rejection Probability; GARCH Models; T-Student Test